Digitalisasi Perangkat Ukur Tinggi dan Berat Badan Balita pada Posyandu Padasuka Kecamatan Cimahi Tengah, Jawa Bara - Nugroho, Hertog; Satria, Ferry; Megiyanto, Griffani; Hanifatunnisa, Rifa; Rahayu, Maya; Hanafi, Usman; Gani, Mina Naidah (Politeknik Negeri Madiun, 2021)
Posyandu activities, which include measuring height and weight, have become a routine for monitoring the growth and development of toddlers. Height and weight are important parameters in toddler development related to the prevention of malnutrition that can lead to stunting and other possible disorders.In general, Posyandu activities, in Indonesia, especially posyandu RW 14 Padasuka, Cimahi Tengah sub-district, are still carried out conventionally using cards to record data. There are many problems with data loss among parents due to inadequate documentation and a lot of data storage at the Posyandu which makes recorded data difficult to find when the data is needed. Measurement of height and weight that still uses conventional scales operated by Posyandu officers also makes the measurement results for each child can be different.Through Community Service program, we proposed to develop and implement a weight and height measurement device based on Arduino and a website. Data from these two parameters can be displayed on a web page that can be accessed by parents of Posyandu participants. The development of the tool has been successfully realized and the test shows an error of 0.19% and 0.88% compared to the measurement of manual tools (rulers and scales).Training with Posyandu Padasuka community partners, Cimahi Tengah has been carried out on September 19, 2020 and was attended by several Posyandu volunteers and local residents. The training went well and the equipment was handed over so that it could be used properly.